Family close but friends closer: exploring social support and resilience in older spousal dementia carers. (2nd November 2017) - Donnellan, Warren J.; Bennett, Kate M.; Soulsby, Laura K.
ABSTRACT: Objectives: Spousal dementia carers have unique support needs; they are likely to disengage from their existing social networks as they need to devote more time to caring as the disease progresses. Previously we showed that support resources can facilitate resilience in carers, but the relationship is complex and varies by relationship type. The current paper aims to explore social support as a key component of resilience to identify the availability, function and perceived functional aspects of support provided to older spousal dementia carers. Method: We conducted 23 in-depth qualitative interviews with spousal carers from two carer support groups and a care home in North West England. Results: Family and friends served a wide range of functions but were equally available to resilient and non-resilient participants. Family support was perceived as unhelpful if it created feelings of over-dependence. Participants were less likely to resist involvement of grandchildren due to their relatively narrow and low-level support functions. Friend support was perceived as most helpful when it derived from those in similar circumstances. Neighbours played a functionally unique role of crisis management. These perceptions may moderate the effect of support on resilience. Conclusion: Family and friend support is not always sufficient to facilitate resilience. Support functions facilitate resilience only if they are perceived to match need. Implications of these findings are discussed.